A clinical survey about commercial games in lower limb prosthetic rehabilitation. (June 2018) - Imam, Bita; Miller, William C; Finlayson, Heather C; Eng, Janice J; Jarus, Tal
Background: Despite the popularity of commercial games in lower limb prosthetic rehabilitation, data about their prevalence of use as well as therapists' perspectives about these games are still lacking. Objectives: To learn about the prevalence of use of commercial games in lower limb prosthetic rehabilitation and therapists' perspectives about these games. Study design: Cross-sectional. Methods: An online survey was sent to physical and occupational therapists across prosthetic rehabilitation facilities in Canada. The survey had questions about the use of commercial games and therapists' perspectives. Results: Data were collected from 82 therapists. Overall, 46.3% (38/82) reported that they use commercial games; of those, 94.7% (36/38) used the Nintendo Wii Fit. The most reported perceived benefits were the Wii Fit helping to improve weight shifting ( n  = 76/82, 92.7%) and balance ( n  = 75/82, 91.5%), and being motivating and complementing traditional therapy ( n  = 75/82, 91.5%). The most reported perceived barriers/challenges were lack of time and familiarity with the games ( n  = 58/82, 70.7%). Conclusion: Commercial games, particularly the Wii Fit, are commonly used in lower prosthetic rehabilitation in Canada. Most of the queried therapists view the Wii Fit positively. Knowledge translation activities and developing standard treatment protocols would be helpful in minimizing the barriers identified in this study. Clinical relevance: The Wii Fit is prevalent in lower limb prosthetic rehabilitation in Canada and it is viewed positively by therapists as having the potential to improve balance and weight bearing, making rehabilitation more motivating, and complementing traditional therapy. Future studies should investigate the efficacy of the Wii Fit in prosthetic rehabilitation.